Myeloid folliculin balances mTOR activation to maintain innate immunity homeostasis - Li, Jia (JCI Insight, 2019)
The mTOR pathway is central to most cells. How mTOR is activated in macrophages and how it modulates macrophage physiology remain poorly understood. The tumor suppressor folliculin (FLCN) is a GAP for RagC/D, a regulator of mTOR. We show here that LPS potently suppresses FLCN in macrophages, allowing nuclear translocation of the transcription factor TFE3, leading to lysosome biogenesis, cytokine production, and hypersensitivity to inflammatory signals. Nuclear TFE3 additionally activates a transcriptional RagD-positive feedback loop that stimulates FLCN-independent canonical mTOR signaling to S6K and increases cellular proliferation. LPS thus simultaneously suppresses the TFE3 arm and activates the S6K arm of mTOR. In vivo, mice lacking myeloid FLCN reveal chronic macrophage activation, leading to profound histiocytic infiltration and tissue disruption, with hallmarks of human histiocytic syndromes, such as Erdheim-Chester disease. Our data thus identify a critical FLCN-mTOR-TFE3 axis in myeloid cells, modulated by LPS, that balances mTOR activation and curbs innate immune responses.